Effect of SOCO–SAP on moisture of different graded coal gangue and Elymus Dahuricus growth in alpine mining area - Zhilong SUN; Jianying YANG; Changqing SHI; Cheng LI; Ruijie LI; Xiaozhan WANG; Chunyan YANG; Monan DENG; Xinrui YANG; Jiajing LI (Meitan xuebao)
The poor water-holding capacity of coal gangue is the main obstacle factor affecting plant growth. In order to improve the water-holding capacity of coal gangue matrix, the water content of reconstructed coal gangue matrix and the growth characteristics of Elymus dahuricus are studied from three aspects: SOCO–SAP (Polymers are commonly used as water-retaining materials, hereinafter referred to as SAP) mass fraction, bulk density and particle size distribution of coal gangue, and the material parameters suitable for the reconstruction of water-holding layer in the alpine mining area are selected. The results show that: The use of SAP significantly increases the saturated water content, capillary water content and field water holding capacity of coal gangue. Under the same bulk density and gradation, the content is positively correlated with the use of SAP. The SAP can reduce the infiltration rate of coal gangue. The higher the amount of SAP used, the stronger the ability to inhibit water infiltration. At the same mass fraction, the wetting front of different graded coal gangue reaches the bottom of the soil column. The time from short to long is partial sand < partial soil < partial viscosity. When the mass fraction of SAP is 0.1% and 0.2%, the volumetric water content of coal gangue with different gradations at each depth increases slightly, but the effect of using 0.3% and 0.4% is obvious, And there is no significant difference between the two, indicating that when the SAP is used appropriately, the water migration effect of coal gangue is the best. With the increase of SAP dosage, the biomass of Elymus dahuricus in different graded coal gangue substrates is in the order of partial soil > partial sand > partial viscosity. Under a partial soil gradation, when the SAP dosage is 0.3%, the biomass is the largest. Therefore, it is suggested that the bulk density of 1.3 g/cm3, partial soil gradation (2∶2∶2∶2∶2), and the SAP mass fraction of 0.3% should be the main matrix ratio for the construction of water-retaining layer in the alpine mining area, followed by the bulk density of 1.3 g/cm3, partial soil or partial sand gradation, and the SAP usage of 0.3% or 0.4%. These ratios have a better water retention performance, but the plantability is weaker than the former. The results can provide a theoretical basis and technical support for the ecological restoration of alpine soilless mining areas, and provide a reference for land reclamation and solid waste resource utilization in similar typical mining areas.